SOUTH AFRICA’S MARITIME FOREIGN POLICY: A CONCEPTUAL FRAMEWORK - van Nieuwkerk, Anthoni; Manganyi, Calvin (Scientia Militaria - South African Journal of Military Studies, 2020)
In October 2017, South Africa assumed the prestigious chair of the Indian Ocean Rim Association (IORA) for two years. At the time, observers questioned whether this was geared to lead and extract maximum benefit for its members and the country itself. The country’s foreign policy paper of 2011 noted the existence of the Indian Ocean Rim (IOR) but proposed no integrated strategic plans, save to call for a maritime security policy for Africa. The observers did not have to wait long for a response. At the opening of the seventeenth meeting of the IORA Council of Ministers in October, former South African Minister of International Relations and Co-operation, Ms Maite Nkoana-Mashabane, laid out a strategy to promote the Indian Ocean as a zone of peace, stability and development. In doing so, she noted three priorities: maritime safety and security, enhanced disaster risk management, and sustainable and responsible fisheries management. Soon after, tropical Cyclone Idai hit Africa.